2013
DOI: 10.1089/fpd.2013.1559
|View full text |Cite
|
Sign up to set email alerts
|

Optimization of Antimicrobial Combined Effect of Organic Acids and Temperature on Foodborne Salmonella and Escherichia coli in Cattle Feed by Response Surface Methodology

Abstract: Despite the importance of feedstuffs and feed ingredients in the food chain, few studies have analyzed the effectiveness of usual methods for the microbial decontamination of feeds. This work aimed to study the combined effect of temperature and organic acids (formic or lactic) on the inactivation of 10 isolates of Salmonella enterica and Escherichia coli obtained from vegetable feed ingredients, including cereals and other processed materials, in cattle feed. A central composite design was used with acid conc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 20 publications
0
8
0
Order By: Relevance
“…For thermal inactivation experiments, 1 g acidified feed was used to fill devices specifically designed to perform the kinetics . These devices (3 mm thick and 45 mm of internal diameter), consisting of a flat rubber O‐ring completely sealing two aluminum layers, were submerged in a thermostatically controlled water bath at the same temperatures assayed in PBS.…”
Section: Methodsmentioning
confidence: 99%
“…For thermal inactivation experiments, 1 g acidified feed was used to fill devices specifically designed to perform the kinetics . These devices (3 mm thick and 45 mm of internal diameter), consisting of a flat rubber O‐ring completely sealing two aluminum layers, were submerged in a thermostatically controlled water bath at the same temperatures assayed in PBS.…”
Section: Methodsmentioning
confidence: 99%
“…Baek, Kim, & Ha () revealed that the interaction of ET and concentration may also depend on the surface materials because, in predictive models for the reduction of Escherichia coli using Cl treatment, the interaction was significant on stainless steel, plastic, glass, and ceramic, but insignificant on wood and rubber. Amado, Vázquez, Fuciños, MéNDEZ, & Pastrana () studied the combined effect of temperature and LA on the inactivation of Salmonella Enterica and found that only temperature showed as a quadratic coefficient. However, in the present study, each of the factors (Cl, LA, and ET) interacted with EtOH and resulted in significant ( p < .05) reduction of Salmonella biofilms.…”
Section: Resultsmentioning
confidence: 99%
“…Baek, Kim, & Ha (2012) revealed that the interaction of ET and concentration may also depend on the surface materials because, in predictive models for the reduction of Escherichia coli using Cl treatment, the interaction was significant on stainless steel, plastic, glass, and ceramic, but insignificant on wood and rubber. Amado, V azquez, Fuciños, M eNDEZ, & Pastrana (2013) The analysis of variance of the regression parameters of the predicted response surface quadratic model for reduction of Salmonella biofilm on stainless steel is shown in Table 3. The coefficient of determination (R 2 ) and the adjusted coefficient of determination (R 2 adj ) were .8019 and .7902, respectively.…”
Section: Results a Nd Discussionmentioning
confidence: 99%
“…The most common organic acids incorporated into feed include propionic, formic, lactic, and acetic acids. All these organic acids have been shown to be effective at reducing Salmonella in various feed and food matrices (Amado et al, 2013;Anang et al, 2007;Koyuncu et al, 2013;Menconi et al, 2013). Propionic acid has been shown to destroy 90% of the cell population within 1 h and formic acid within 3 h of treatment (Cherrington et al, 1991).…”
Section: Chemical Methodsmentioning
confidence: 99%